Czego chciałbym nauczyć studentów studiów społecznych = What i would like to teach to students of social sciences - Hajduk, Edward (1932-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the consequences of the division of problems into: a/ main and b/ detailed, and the division of hypotheses into: c/ general and d/ detailed. It also shows the consequences of the assumption about the equivalence of conditions listed in detailed hypotheses in order to maintain or reject the general hypothesis.
Keywords: nauki społeczne